PROGRAM JAMINAN HARI TUA BPJS KETENAGAKERJAAN SEBAGAI BENTUK PERLINDUNGAN HUKUM KEPADA PESERTA TERHADAP PEMBERI KERJA - Sari, Masayu Nilam Permata; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research aims to analyze legal protection for old age insurance participants through a study of applicable laws and regulations and related legal concepts. The approach used is the Statute Approach, which analyzes Law no. 40 of 2004 concerning the National Social Security System (SJSN) and Law no. 24 of 2011 concerning the Social Security Administering Body (BPJS), as well as the Conceptual Approach which explores the theories of legal protection, social welfare and employer responsibility. The focus of this research is the role of BPJS Employment as implementer of old age insurance and the obligations of employers in protecting workers' rights. The research results show that although existing regulations have provided a strong legal basis, implementation in the field still faces various challenges, such as low employer compliance and less than optimal supervision by BPJS Employment. This research suggests improvements in law enforcement and supervision of the implementation of employer obligations so that the rights of old age insurance participants can be effectively protected. Apart from that, synergy between the government, BPJS Employment and employers is very necessary to strengthen the social security system in Indonesia.Keywords: Legal, Protectionold age security, BPJS Employment, Employer Obligation.